Hubungan Kecanduan Gadget dengan Kesehatan Mental Remaja Awal di SD Katolik St. Fransiskus Xaverius Pineleng, Kabupaten Minahasa, Sulawesi Utara - Ria Angelina Jessica Rotinsulu (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
Advances in information technology have significantly increased gadget use among children and adolescents. Excessive and unsupervised gadget use may lead to addictive behaviors that adversely affect mental health, including emotional problems, behavioral disorders, hyperactivity, and difficulties in peer relationships. This study aimed to analyze the relationship between gadget addiction and the mental health of early adolescents at St. Francis Xavier Catholic Elementary School, Pineleng. A quantitative observational analytic study with a cross-sectional design was conducted. Data were collected in June 2026 from 49 students selected through total sampling. Gadget addiction was measured using the Smartphone Addiction Scale–Short Version (SAS-SV), while mental health was assessed using the Strengths and Difficulties Questionnaire (SDQ). Data were analyzed using univariate and bivariate statistics with the Chi-square test at a significance level of α = 0.05. Most respondents were 10 years old (57.1%), enrolled in Grade 5 (55.1%), and male (53.1%). High gadget addiction was identified in 75.5% of respondents. Based on SDQ scores, 61.2% had normal mental health, 18.4% were borderline, and 20.4% were abnormal. The Chi-square test showed no significant relationship between gadget addiction and mental health (p = 0.774). In conclusion, gadget addiction was not significantly associated with the mental health of early adolescents. Nevertheless, continuous supervision by parents and schools is essential to encourage healthy and balanced gadget use that supports children's psychological well-being and social development.